MiR-12200-5p Targets Multiple Members of Wnt Signaling Pathway to Inhibit Osteoblast Differentiation and Bone Formation - Li, Hui; Yin, Chong; Li, Jingjia; Huang, Qian; Huai, Ying; Chu, Xiaohua; Ji, Mili; Tian, Ye; Qian, Airong; Li, Danming (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: Osteoporosis is widespread and has become an emerging problem in the elderly. MicroRNAs could affect osteoblast differentiation and further regulate the occurrence of osteoporosis by targeting osteogenic differentiation signaling pathways. Our screening study found that miR-12200-5p simultaneously targeted six important factors within the Wnt signaling pathway (Apc, Tcf4, Tcf7, Wnt3a, Wnt5a, and Lrp6), indicating that miR-12200-5p might function as a strong regulator of this pathway. Since the Wnt pathway exists as one of the most essential pathways for osteogenic differentiation, miR-12200-5p may have an important role in the development of osteoporosis. Objective: This study intended to explore the regulatory role and corresponding mechanism of miR-12200-5p in osteoblast differentiation. Methods: We investigated the differentiation of osteoblast after the treatments of miR-12200-5p mimic and inhibitor. The interactions between miR-12200-5p and its target genes were also detected. Furthermore, the rescue effect of miR-12200-5p inhibitor on osteoporosis was evaluated using an ovariectomized osteoporosis mouse model. Results: MiR-12200-5p significantly inhibited osteoblast differentiation, and bound with the 3’-UTR sequences of its target genes (Apc, Tcf4, Tcf7, Wnt3a, Wnt5a, and Lrp6) to reduce the expressions of these genes. The inhibition of miR-12200-5p would almost fully alleviate postmenopausal osteoporosis. Conclusion: MiR-12200-5p could strongly repress osteoblast differentiation and bone formation by targeting multiple members of the Wnt signaling pathway simultaneously. The study supplemented the theoretical and experimental basis for researching the mechanism of osteogenic differentiation and inspired the development of novel therapeutic strategies for osteoporosis.
Keywords: Wnt signaling pathway